2007
DOI: 10.1897/1551-3793(2007)3[3:aurrar]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Animal Use Replacement, Reduction, and Refinement: Development of an Integrated Testing Strategy for Bioconcentration of Chemicals in Fish

Abstract: When addressing the use of fish for the environmental safety of chemicals and effluents, there are many opportunities for applying the principles of the 3Rs: Reduce, Refine, and Replace. The current environmental regulatory testing strategy for bioconcentration and secondary poisoning has been reviewed, and alternative approaches that provide useful information are described. Several approaches can be used to reduce the number of fish used in the Organization for Economic Cooperation and Development (OECD) Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 81 publications
1
41
0
Order By: Relevance
“…This information has substantial value for prioritizing limited testing resources and may provide important support for bioaccumulation assessments within the context of a weightof-evidence approach [54]. Eventually, we expect these or similar methods to be endorsed by governmental regulatory authorities as part of a tiered approach to bioaccumulation assessment [54,55]. To achieve this goal it will be necessary to evaluate the models using well-matched (same species, life stage, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This information has substantial value for prioritizing limited testing resources and may provide important support for bioaccumulation assessments within the context of a weightof-evidence approach [54]. Eventually, we expect these or similar methods to be endorsed by governmental regulatory authorities as part of a tiered approach to bioaccumulation assessment [54,55]. To achieve this goal it will be necessary to evaluate the models using well-matched (same species, life stage, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, it does suggest that once the MW is in the region of 700-1100, depending on other factors, a reduced BCF may be expected. Hence, while recognizing the uncertainties in the interpretation of experimental results, de Wolf et al [43] recommended that to demonstrate a reduced BCF a substance should have either:…”
Section: Molecular Weightmentioning
confidence: 99%
“…In conclusion, there would appear to be no clear cut-off value for molecular size beyond which no absorption will take place. While recognizing the uncertainties in the interpretation of experimental results, de Wolf et al [43] Lipinksi's rule of 5 Lipinski et al [54] identified five physical chemical characteristics that influence solubility and absorption across the mammalian intestinal lumen using more than 2,200 drug development tests. These characteristics have been rigorously reviewed [55,56] and are used to develop commercial models to estimate absorption in mammals.…”
Section: Molecular Sizementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the simplicity of zebrafish behavioral paradigms helps reduce possible stress to the animal and time it is subjected to testing. The aquatic paradigms adhere to the 3Rs principle (de Wolf et al, 2007), as fish are less sentient than rodents, and typically use less invasive administration of drugs (i.e., immersion/inhalation vs. injections). Furthermore, unlike rodent developmental models of stress, zebrafish embryos can be exposed to neonatal stressors without having to consider the environmental effects on the mother (Teraoka et al, 1993).…”
Section: W Hy Use Zebrafish For Neurobehavioral Research?mentioning
confidence: 99%